Allogeneic hematopoietic cell transplantation in chemotherapy‐induced aplasia in children with high‐risk acute myeloid leukemia or myelodysplasia. Issue 1 (14th October 2018) - Kussman, Ashleigh; Shyr, David; Hale, Gregory; Oshrine, Benjamin; Petrovic, Aleksandra
Abstract: Relapse remains the most common cause of treatment failure after hematopoietic cell transplantation for acute myeloid leukemia. Inability to achieve hematologic complete remission has been a barrier to transplant for patients with refractory disease. We describe six children with refractory myeloid disease undergoing transplant in chemotherapy‐induced aplasia, as a strategy to facilitate curative therapy in refractory patients. Clofarabine‐ or high‐dose cytarabine‐based chemotherapy regimens were used to achieve marrow aplasia, followed by reduced‐intensity conditioning and allogeneic transplant before hematologic recovery. Long‐term disease control was achieved in five, with one transplant‐related mortality, suggesting the feasibility of this approach.